META-ANALISIS: PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK TERINTEGRASI SCIENCE, TECHNOLOGY, ENGINEERING, ARTS, AND MATHEMATICS UNTUK PESERTA DIDIK FASE F - Humaira, Astri; Zulyusri, Zulyusri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to improve the feasibility and effectiveness of Student Worksheets (LKPD) based on the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach through a meta-analysis method. This study examines nine selected articles published between 2020 and 2024, focusing on the practicality value of each LKPD developed. The results of the analysis show that STEAM-based LKPD has a high level of practicality, with scores ranging from 82% to 93%. The STEAM approach integrated into LKPD has been proven to be able to develop critical thinking skills, creativity, and problem-solving skills of students, and is flexible for use at various levels of education and subjects. Therefore, STEAM-based LKPD is considered worthy of being used as an effective learning medium in supporting active and contextual learning processes.